NET-02 trial protocol: a multicentre, randomised, parallel group, open-label, phase II, single-stage selection trial of liposomal irinotecan (nal-IRI) and 5-fluorouracil (5-FU)/folinic acid or docetaxel as second-line therapy in patients with progressive poorly differentiated extrapulmonary neuroendocrine carcinoma (NEC). Issue 2 (5th February 2020) - Craig, Zoe; Swain, Jayne; Batman, Emma; Wadsley, Jonathan; Reed, Nicholas; Faluyi, Olusola; Cave, Judith; Sharma, Rohini; Chau, Ian; Wall, Lucy; Lamarca, Angela; Hubner, R; et al.
Abstract : Introduction: Poorly differentiated (PD), extrapulmonary (EP), neuroendocrine carcinomas (NECs) are rare but aggressive neuroendocrine neoplasms. First-line treatment for advanced disease is an etoposide and platinum-based chemotherapy combination. There is no established second-line treatment for patients with PD-EP-NEC, and this is an area of unmet need. Methods and analysis: NET-02 is a UK, multicentre, randomised (1:1), parallel group, open-label, phase II, single-stage selection trial of liposomal irinotecan (nal-IRI)/5-fluorouracil (5-FU)/folinic acid or docetaxel as second-line therapy in patients with progressive PD-EP-NEC. One hundred and two eligible participants will be randomised to receive either nal-IRI/5-FU/folinic acid or docetaxel. The primary objective is to determine the 6-month progression-free survival (PFS) rate. The secondary objectives of this study are to determine PFS, overall survival, objective response rate, toxicity, quality of life and whether neuron-specific enolase is predictive of treatment response. If either treatment is found to have a 6-month PFS rate of at least 25%, that treatment will be considered for a phase III trial. If both treatments meet this target, prespecified selection criteria will be applied to establish which treatment to take forward. Ethics and dissemination: This study has ethical approval from the Greater Manchester Central Research Ethics Committee (reference no. 18/NW/0031) and clinical trial authorisation from the Medicine and Healthcare Products Regulatory Agency. Results will be published in peer-reviewed journals and uploaded to the European Union Clinical Trials Register. Trial registration numbers: ISRCTN10996604, NCT03837977, EudraCT Number: 2017-002453-11